Effectiveness of goat testicle meal on sex reversal of betta fish (Betta sp.) - Ramadhan, Muhammad Rizqy; Haser, Teuku Fadlon; Putriningtias, Andika; Harahap, Antoni; Febri, Suri Purnama (Universitas Malikussaleh, 2024)
The male Betta fish is said to be special because it has a unique body shape and beautiful colours, so it is very popular among people who love ornamental fish. This research aims to analyze the effectiveness of giving goat testicle flour on sex reversal in betta fish. The research design carried out was a Completely Randomized Design (CRD). consisting of 4 treatments with 3 repetitions. During the 60-day rearing period, silkworms and artemia were given food. The results of the study showed that the effect on goat testicles had a significant effect on the male sex ratio and survival of betta fish, with a male sex ratio value of 74.92% and survival of 97.77%. Water quality during the research supports the male sex ratio and the survival of betta fish.Keywords: Betta Fish; Goat Testicular Meal; Male Sex Ratio, Sex Reversal; Survival